Gender differences in acute coronary syndrome: experience from the Croatian branch of the ISACS-CT registry. (25th November 2020) - Loncaric, F; Mjehovic, P; Sabljak, D; Vlahovic, V; Vinkovic, I; Radic, T; Klaric, K; Dakic, A; Adamovic, I; Bunic, M; Pavasovic, S; Jakus, N; et al.
Abstract: Background and aim: In recent years, worse outcomes of female acute coronary syndrome (ACS) patients have been recognized. The aim was to explore gender differences in ACS in the Croatian branch of the ISACS-CT registry (NCT01218776). Methods: From January 2012 to May 2018, 3066 ACS patients were enrolled; 50% (n=1539) presenting with STEMI, 35% (n=1071) with NSTEMI, and 15% (n=456) with unstable angina (UA). In-hospital mortality was defined as the primary endpoint. Results: At admission women were older, more burdened with comorbidities, with a longer delay from symptom onset to admission (Figure 1), but without differences in signs and symptoms or Troponin T levels (p=0.166). During hospitalization, there were no gender difference in the administration of beta blockers, ACE inhibitors or statins in the first 24 hours. Coronary angiography was performed in a smaller percentage of female patients (86 vs. 92%, p<0.001), however, the finding of no significant stenosis was more common in women (6 vs. 2%, p<0.001). Furthermore, less women underwent primary PCI (pPCI) (67 vs. 77%, p<0.001). While there were no gender differences in the number of the treated lesions (p=0.978), women had a higher incidence of procedural pPCI complications compared to men (13 vs. 8%, p=0.001) – predominantly due to higher occurrence of no reflow, side branch loss and new thrombus formation. Multivariate regression showed gender was not associated with the decision not to perform pPCI, whereas age over 65 years (OR=1.75), diabetes (OR=1.30), hypertension (OR=1.55), chronic kidney disease (OR=2.06) and the delay from onset of symptoms to admission >6h (OR=1.61) were associated. At discharge, there were no gender differences in LV ejection fraction <40% (p=0.259). Women with STEMI had significantly higher in-hospital mortality (10 vs. 4%, p<0.001), whereas no gender differences were seen regarding unstable angina and NSTEMI. After multivariate regression, only age over 65 years (OR=3.61), chronic kidney disease (OR=1.85) and primary PCI (OR=0.49) remained associated with in-hospital mortality. Conclusion: The findings in the Croatian branch of the ISACS-CT registry demonstrate notable gender differences in ACS. Older age and a substantial burden of comorbidities represent strong influences on disease development, intervention choice and in-hospital mortality when treating women with ACS. Funding Acknowledgement: Type of funding source: None